The Qualitative Review of Human Security in South Africa: A Four Levels Analysis (The Strategic Review for Southern Africa, 2021)
Post-1994 South Africa is founded on values of human dignity, equality and ensuring fundamental human rights for all which are enshrined in its democratic constitution. This comes as the advent of democracy in South Africa from the apartheid past coincided with the advancement of the United Nations Development Programme’s (UNDPs) reconfigured concept of security from a state-centric to a people-focused ideal. The new concept of human security integrates all rights, needs and security of men together with aspirations for sustainable and inclusive development. It advocates for the protection and empowerment of people against threats to their lives, something that the apartheid state failed to do as it was the main orchestrator of human insecurity in the country. Likewise, the article is a qualitative review of the role that human security has played in post-South Africa’s policymaking decisions using the level of analysis approach. The four levels feature the individual, local/provincial, domestic/state and global analysis. These levels of analysis help in shedding qualitative understanding of how a single dynamic in socio-political empowerment affects another. It concludes that despite the notion of human security being widely articulated as a conceptual basis for the country’s official documents, it lacks de facto operational power to shaping actual policy actions.